High gradient ultra-high brightness C-band photoinjector optimization. (July 2020) - Croia, M; Alesini, D; Cardelli, F; Diomede, M; Ferrario, M; Giribono, A; Romeo, S; Vaccarezza, C; Vannozzi, A
Abstract: Cathode, laser system, high RF peak field, and gun solenoid are fundamental aspects that have to be optimized to produce high brightness beam in photoinjectors. In order to produce ultra-high brightness beams of about one order of magnitude more than the present devices, new studies have been done in the last years. One promising approach is to increase the peak field on the cathode surface. In this paper we will present a study on a C-band gun using a cathode peak field of 240 MV/m. A first RF study to reach such very high field was done, by means of shortening the RF pulse duration. A first design of the RF structures and solenoid was carried out. If we will not reach exactly the predicted gradient during the RF tests, the impact on the beam dynamics have been simulated reducing the peak field on the cathode up to the value of 130 MV/m, maintaining the same geometry. The convenience of such gun also at a lower gradient, opened the way to possible applications on light production devices. For example, this C-band injector is one of the main options to guide the X-band linac in the CompactLight design study, where an X-ray FEL is foreseen.